Pós-modernismo na narrativa do filme O grande Lebowski (1998) - Silva, Lucas Vian e (2018)
This research presents as object of study the film The Big Lebowski (Ethan e Joel Coen; 1998) and investigates the influence of postmodernism in its narrative. Initially, it verifies which cinematographic genres are inserted in the narrative by the movie directors, Joel and Ethan Coen, next, it conceptualizes the postmodernism as a cinematographic tendency; and finally, it identifies movie segments that refer to classic Hollywoodian genres and the filmography of classical directors. It is a bibliographical research on filmography genres and the postmodern tendency. Besides the conceptual research, the approach includes the internal analysis of the narrative, from the genre segmentation. The theoretical references of Ebert (1998) and Freisleben (2010) deal with the filmography of Coen brothers; Bergan (2011), Aumont and Marie (2006), Schatz (1981) and Lira (2015) contribute to the understanding of cinematography genres; Harvey (2008) and Hall (2011) address the concept of postmodernism in a cultural and social bias; Hutcheon (1991) and Lyotard (2009) discuss the legitimacy of postmodern culture; Bordwell and Thompson (2013) conceptualize the basic elements that compose the plot and, finally, Pucci Jr. (2006, 2008) and Jameson (1985) bring the postmodernism applied to the cinema. The hypothesis of this research is that the work studied can be considered postmodern because of its mixture of different genres and the signalization of the end of the great narratives.